Die Violencia in Kolumbien: verbotene Erinnerung? Der Bürgerkrieg in Politik und Gesellschaft, 1948-2008 - Schuster, Sven (Historamericana, 2022)
The Colombian civil war of the 1940s and 50s - La Violencia - is still having an impact today. In contrast to previous Violencia studies, which mostly focused on the course of the war, the author attempts to trace the historical politics of the political elite from the 1950s to the present day.